HyScreen: A Ground-Based Imaging System for High-Resolution Red and Far-Red Solar-Induced Chlorophyll Fluorescence - Huaiyue Peng; Maria Pilar Cendrero-Mateo; Juliane Bendig; Bastian Siegmann; Kelvin Acebron; Caspar Kneer; Kari Kataja; Onno Muller; Uwe Rascher (Sensors, 2022)
Solar-induced chlorophyll fluorescence (SIF) is used as a proxy of photosynthetic efficiency. However, interpreting top-of-canopy (TOC) SIF in relation to photosynthesis remains challenging due to the distortion introduced by the canopy’s structural effects (i.e., fluorescence re-absorption, sunlit-shaded leaves, etc.) and sun–canopy–sensor geometry (i.e., direct radiation infilling). Therefore, ground-based, high-spatial-resolution data sets are needed to characterize the described effects and to be able to downscale TOC SIF to the leafs where the photosynthetic processes are taking place. We herein introduce HyScreen, a ground-based push-broom hyperspectral imaging system designed to measure red (<semantics>F687</semantics>) and far-red (<semantics>F760</semantics>) SIF and vegetation indices from TOC with single-leaf spatial resolution. This paper presents measurement protocols, the data processing chain and a case study of SIF retrieval. Raw data from two imaging sensors were processed to top-of-canopy radiance by dark-current correction, radiometric calibration, and empirical line correction. In the next step, the improved Fraunhofer line descrimination (iFLD) and spectral-fitting method (SFM) were used for SIF retrieval, and vegetation indices were calculated. With the developed protocol and data processing chain, we estimated a signal-to-noise ratio (SNR) between 50 and 200 from reference panels with reflectance from 5% to 95% and noise equivalent radiance (NER) of 0.04 (5%) to 0.18 (95%) mW m<semantics>−2</semantics> sr<semantics>−1</semantics> nm<semantics>−1</semantics>. The results from the case study showed that non-vegetation targets had SIF values close to 0 mW m<semantics>−2</semantics> sr<semantics>−1</semantics> nm<semantics>−1</semantics>, whereas vegetation targets had a mean <semantics>F687</semantics> of 1.13 and <semantics>F760</semantics> of 1.96 mW m<semantics>−2</semantics> sr<semantics>−1</semantics> nm<semantics>−1</semantics> from the SFM method. HyScreen showed good performance for SIF retrievals at both <semantics>F687</semantics> and <semantics>F760</semantics>; nevertheless, we recommend further adaptations to correct for the effects of noise, varying illumination and sensor optics. In conclusion, due to its high spatial resolution, Hyscreen is a promising tool for investigating the relationship between leafs and TOC SIF as well as their relationship with plants’ photosynthetic capacity.